MIRERC 036/2025: DETERMINANTS OF SEVERE ACUTE MALNUTRTION AMONG CHILDREN AGED 6-59 MONTHS, MARSABIT COUNTY, KENYA. - NATUWAKI, BENEDICT LNGERIYON; Dr Kubai P.K; Dr Kagendo Dorothy (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
ABSTRACT Severe Acute Malnutrition (SAM) remains a significant global health issue, with 17 million children affected, and Africa contributing to 46% of the related deaths. In Kenya, ASAL counties like Marsabit have some of the highest rates of SAM. SAM is a life-threatening condition caused by deficiencies in protein, calories, and essential micronutrients. The World Health Organization (WHO) reports that 19 million children under five years old are affected globally, with over 400,000 deaths annually attributed to SAM.This study aims to investigate the risk factors influencing severe acute malnutrition among children aged 6–59 months in Marsabit County. Specifically, the study seeks to determine the socioeconomic factors contributing to SAM, assess the role of maternal nutrition and health status in increasing the risk of SAM in infants and young children, examine the influence of dietary practices on SAM, and investigate how healthcare services and the utilization of preventive health measures impact the risk of SAM in the region. A cross-sectional and case-control design will be employed with a sample size of 385 respondents, selected through simple random and purposive sampling methods. Data will be collected using structured questionnaires, clinical record checklists, and Key Informant Interviews (KIIs) with healthcare professionals. The data will be cleaned, coded, and analysed using SPSS version 28. Descriptive statistics will summarize the demographic and health characteristics, while inferential statistics, such as ordinary least squares regression, will be used to assess the relationships between the identified risk factors and SAM at a 0.05 significance level.